Third sector perspectives on community link worker referrals in social prescribing: a realist analysis - Allbutt, Helen; Maciver, Donald; Leitch, Alison; Crandles, Anne; Fitzpatrick, Linda Irvine (Frontiers in Public Health, 2025)
IntroductionCommunity link workers (CLWs), also known as social prescribing link workers, connect individuals to community support, much of which is provided by third-sector organisations (TSOs). TSOs are common referral destinations for CLWs, yet the relationships between CLWs and TSOs remain under-explored.MethodThis realist study investigated TSOs’ perceptions of link working, focusing on referral and collaboration dynamics. Conducted across 22 TSOs in Scotland, it involved in-depth interviews with TSO staff and consultations with CLWs and managers, analysing data via realist heuristics to identify contexts, mechanisms, and outcomes.ResultsTargeted referrals by experienced CLWs, with follow-up, and strong TSO-CLW relationships, improved client health, wellbeing, and independence while reducing reliance on statutory services. These processes fostered professionals’ trust, satisfaction, and innovation, creating a positive feedback loop. Conversely, inconsistent referrals, such as over-referral or scattergun approaches, compounded by resource constraints and perceptions of inequitable partnerships, led to suboptimal client outcomes, dissatisfaction, and weakened collaboration. Important contexts included extreme resource pressures, varying CLW expertise, and perceptions of power imbalances.DiscussionEffective social prescribing needs sustained TSO-CLW collaboration, supported by third-sector investment and tools for equitable partnerships. Rather than a referral process, social prescribing should be envisioned as a community of practice, defined by relationships, a common purpose and shared responsibility for challenges and solutions. Future models should prioritise strengthening statutory and third-sector trust and collaboration.